'Fitted both Morally and Physically to Fulfil his Proper Duties in the Battle of Life'? – The Effectiveness or Otherwise of Penal Servitude and Imprisonment 1853–2021. (11th October 2021) - COX, DAVID J.
Abstract: This article is a response to two questions posed in an article published in the first volume of the Howard Journal. That article asked, 'should penal servitude be abolished?' and also discussed the merits of 'preventive detention', in which so‐called 'habitual' criminals could be imprisoned for up to ten years after their original sentence had expired, in order to keep the public safe for an extended time. The current article therefore looks at the limitations and problems of penal servitude (which operated from 1853 until 1948) together with a brief examination of the success or otherwise of preventive detention.